Trends in age at first sex in Uganda: evidence from Demographic and Health Survey data and longitudinal cohorts in Masaka and Rakai. (23rd March 2009) - Slaymaker, E; Bwanika, J B; Kasamba, I; Lutalo, T; Maher, D; Todd, J
Abstract : Objectives: To derive the best possible estimates of trends in age at first sex (AFS) among successive cohorts of Ugandan men and women based on all the data available from the Demographic and Health Surveys (DHS) and cohort studies in Masaka and Rakai districts. Methods: The datasets from the DHS, Masaka cohort and Rakai cohort were analysed separately. Survival analysis methods were used to estimate median AFS for men and women born in the 1950s–1980s and to compute hazard ratios for first sex, comparing later cohorts with earlier cohorts. Results: The DHS and Masaka data showed an increase in AFS in women in the more recent birth cohorts compared with those born before 1970, but this was less apparent in the Rakai data. Successive male cohorts in Masaka appeared first to have an increased AFS which subsequently decreased, a trend that was also apparent (but not significant) in the DHS data. Younger men in Rakai had an earlier AFS than those born before 1980. Conclusions: Women in Uganda who were born after 1970 have, on average, had sex at a later age than those born earlier. For men, AFS has not changed consistently over the period in question. Differences between Masaka and Rakai may reflect socioeconomic differences. Most of the change in AFS occurred too late to have contributed to the initial decline in the incidence of HIV.